2011
DOI: 10.1002/hbm.21422
|View full text |Cite
|
Sign up to set email alerts
|

Late effects of high‐dose adjuvant chemotherapy on white and gray matter in breast cancer survivors: Converging results from multimodal magnetic resonance imaging

Abstract: The neural substrate underlying cognitive impairments after chemotherapy is largely unknown. Here, we investigated very late (>9 years) effects of adjuvant high-dose chemotherapy on brain white and gray matter in primary breast cancer survivors (n = 17) with multimodal magnetic resonance imaging (MRI). A group of breast cancer survivors who did not receive chemotherapy was scanned for comparison (n = 15). Neuropsychological tests demonstrated cognitive impairments in the chemotherapy group. Diffusion tensor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
222
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 236 publications
(245 citation statements)
references
References 57 publications
12
222
1
10
Order By: Relevance
“…The only other study that investigated the association between hippocampal volume and chemotherapy did also not observe a relationship between the two [8]. Of all studies that investigated the effect of chemotherapy on brain structure, none examined total tissue volumes after cytotoxic treatment [2][3][4][7][8][9][10]. We found significant effects of chemotherapy on TBV and gray matter volume.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The only other study that investigated the association between hippocampal volume and chemotherapy did also not observe a relationship between the two [8]. Of all studies that investigated the effect of chemotherapy on brain structure, none examined total tissue volumes after cytotoxic treatment [2][3][4][7][8][9][10]. We found significant effects of chemotherapy on TBV and gray matter volume.…”
Section: Discussionmentioning
confidence: 73%
“…Up till now three studies have reported adverse effects of chemotherapy on white matter as measured with diffusion tensor imaging (DTI) [4][5][6]. Therefore, it might be that the small effects of chemotherapy on total gray matter volume may be accompanied by microstructural whitematter changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations